Interdependence of company’s industrial competitive position and its strategic orientation: A dynamic theoretical model - Vladimir Gnjidić (Management : Journal of Contemporary Management Issues, 2018)

(untitled)
This paper offers a conceptual model for revealing dynamic interdependence between company’s competitive position using Porter’s analytical framework “five competitive forces” and its strategic orientation, as defined by Miles and Snow’s strategic typology of organizational behaviour. As both models have been criticized for its static nature not fitting contemporary market dynamism, the proposed reciprocity of interrelationship between industrial structure and company’s conduct in different time periods, provides a modern alternative for making strategic choices. The author suggests a theoretical correlation between company’s previous, current and anticipated competitive positions with its previous, current and planned type of strategic behaviour. Accordingly, dynamically consistent successful strategic types (prospector, analyst, and defender) should be connected to the above average dynamical competitive positions. The proof of existence of such a correlation would indicate company’s consistent ability to successfully adapt to (consistently changing) industrial environment.